The Effectiveness of Cooperative Integrated Reading and Composition on Vocational High School Students' Reading Comprehension (RETAIN, 2023)
The aims of this study are to investigate: (1) the effectiveness of the Cooperative Integrated Reading and Composition method to improve students’ reading comprehension; (2) how students’ perception of using the Cooperative Integrated Reading and Composition method to improve students’ reading comprehension. The method used is quantitative research, with tests and questionnaires to collect the data. The subject is tenth-grade students in one of the vocational high schools in Surabaya who are taken by convenience sampling. The result is analyzed by using: (1) Wilcoxon and (2) Descriptive Statistics. The result showed that: (1) there are significant differences between the pretest and posttest, p = .000 less than 0.05; (2) students believe that CIRC develops their group processing skills more than interpersonal skills. It is indicating that the treatment using the CIRC method could effectively improve students' reading comprehension and gave a positive impact on students in developing their interpersonal skills and group processing skill.